2017
DOI: 10.17977/um044v2i1p1-9
|View full text |Cite
|
Sign up to set email alerts
|

Uji Efektifitas Ekstrak Bawang Putih (Allium Sativum) Sebagai Insektisida Terhadap Kutu Rambut (Pediculus Capitis)

Abstract: Hair lice are small parasites that live by sucking blood in humans. Almost all patients consider the hair tick is a common thing, but if the hair louse is not treated immediately will cause the emergence of Relapsing Fever disease caused by infection in the scalp of the patient. The purpose of this study is to determine the effectiveness of garlic extract with concentrations of 4%, 6%, and 8% as an insecticide against hair lice. The research method used is true experimental or real experiment using sample of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
6
0
8
Order By: Relevance
“…The results of this study were also the same as the study by Sasmilati (4) that reported based on the results of the oneway ANOVA test there were significant differences in the effects of larvicides in the different concentrations of Allium sativum solution groups with p-value <0.05( sig) and found significant differences between groups that was p-value <0.05(sig). The results of a study conducted by Pritacindy, et al (17) showed that Allium sativum proved to be effective as a pediculicide, and a higher concentration of A. sativum extract would be a more effective insecticide for hair lice. The results of research conducted by Al-Zanbagi and Al-Hasdi (18) showed that A. sativum was a strong natural pediculicide, medicinally substance with no toxicity; further, the results also proved that higher concentrations of Allium sativum would kill P.h.capitis more effectively.…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study were also the same as the study by Sasmilati (4) that reported based on the results of the oneway ANOVA test there were significant differences in the effects of larvicides in the different concentrations of Allium sativum solution groups with p-value <0.05( sig) and found significant differences between groups that was p-value <0.05(sig). The results of a study conducted by Pritacindy, et al (17) showed that Allium sativum proved to be effective as a pediculicide, and a higher concentration of A. sativum extract would be a more effective insecticide for hair lice. The results of research conducted by Al-Zanbagi and Al-Hasdi (18) showed that A. sativum was a strong natural pediculicide, medicinally substance with no toxicity; further, the results also proved that higher concentrations of Allium sativum would kill P.h.capitis more effectively.…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%
“…Allium sativum contains metabolite compounds such as allicin, adenosine, ajoene, flavonoids, saponins, tuberholosides, scordinin (10,17), alliin, scordinin, methylene trisulfide, saltivine, essential oils (4). Sulfide derivatives, namely allicin, are stomach poisons that kill the target organism if allicin enters the digestive organs and is absorbed by the intestinal wall (7).…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%
“…Bawang putih (Allium sativum) telah digunakan sebagai pengobatan herbal selama ribuan tahun karena senyawa organosulfur aktif yang terdapat dalam bawang putih. Senyawa organosulfur aktif dalam bawang putih berupa flavonoid, adenosin, ahoene, dan alliin (Pritacindy et al, 2017). Bawang putih yang mentah memiliki rasa yang kuat dan tajam.…”
Section: Hasil Dan Pembahasanunclassified
“…The garlic spray was significant, with a p-value of 0.000. it was in line with research mentioned that 4% garlic solution could kill lice in 0.4450 hours, 6% garlic solution could kill lice in 0.1380 hours, and 8% garlic solution could be an effective insecticide for head lice as mentioned that the higher solution of garlic was the better able to kill head lice or pediculosis capitis. 5 Another researcher also stated that garlic extract is mortal for plant lice (M. persicae). In that research, the 0% garlic solution (control group) could kill 34.67% plant lice, 45% garlic solution killed 54.00% lice, and 60% garlic solution killed 72.33% 10,11 .…”
Section: T H E D I F F E R E N C E O F T H E N a T U R A L I N G R E mentioning
confidence: 99%
“…4 Garlic is effective in killing head lice as it contains ethanol with an 8% concentration. It was proven to e effective in killing head lice within 0.030 hours 5 . Besides, garlic is often used for its antifungal and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%